Thermal lens detection of one and two‐color laser excitation of benzene in cryogenic liquid solutions. (6th April 2015) - Diez‐y‐Riega, Helena; Camejo, David; Manzanares, Carlos E.; Joubert, Pierre; Lavorel, Bruno; Kiefer, Johannes; Moger, Julian
<x xml:space="preserve">Abstract</x> The thermal lens technique is applied to vibrational overtone spectroscopy of cryogenic solutions of benzene. The pump and probe thermal lens technique has been found to be very sensitive for detecting samples of low concentration in transparent liquefied gas solvents at low temperatures. The C–H fifth vibrational (Δυ = 6) overtone of benzene in liquefied ethane, krypton, and argon have been recorded at concentrations between 10 and 58 p.p.m. in a range of temperatures between 87 and 150 K. Experiments with one‐color laser excitation are sensitive enough to detect benzene at parts per million mole fraction. The dependence of the signal on the physical properties of the solvent and the excitation wavelength are shown. Finally, a thermal lens experiment with two‐color laser excitation is presented showing an increase in the magnitude of the peak absorption that will result in an increase of the limit of detection. A three‐level model to explain signal enhancement with respect to one‐color laser excitation under the same experimental conditions is presented. Copyright © 2015 John Wiley & Sons, Ltd.